Peranan Mediasi Inovasi: Pengaruh Orientasi Kewirausahaan, Teknologi, Intensitas Persaingan Terhadap Kinerja Perempuan Muslim Pada UMKM Hasil Olah Melinjo di Menes Banten - M. Fadhli Nursal; Maidani Maidani; Chistophorus Indra Wahyu Putra; Muhammad Richo Rianto; Dinda Nurdianah; Putri Amanda (Jurnal Ilmiah Ekonomi Islam, 2023)
This study analyzes the role of mediation of innovation in the influence of entrepreneurial orientation, technological orientation and intensity of competition on the performance of MSMEs by Muslim women who cultivate melinjo in the village of Menes Pandeglang, Banten. This research uses quantitative methods and statistical analysis tools in the form of smartpls 4.0. This study used a sampling technique in the form of quota sampling as many as 62 female entrepreneurs who processed melinjo. The results of this study found that there was an influence of entrepreneurial orientation and technology on innovation but different results on the intensity of competition. Other results explain that the influence of entrepreneurial orientation and innovation on performance but technology orientation and competition intensity have no effect on performance. The role of mediation has an effect on entrepreneurial orientation and technology on performance but has no effect on the intensity of competition. This research focuses on the role of women in improving the performance of MSMEs processed melinjo. In addition, the focus of this research is on the village of Menes, which is one of the villages in Pandegelang, Banten. The novelty in this study is that apart from the object of research, it is also a research model that has never been studied before.